2015
DOI: 10.1007/s10195-015-0368-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of psychological support in patients undergoing primary total hip or knee arthroplasty: a controlled cohort study

Abstract: BackgroundWe hypothesised that psychological support would have a significant improvement on the mental and physical recovery of patients undergoing primary total hip or knee arthroplasty.Materials and methods200 patients were consecutively alternately assigned (1:1) to receive routine care (control group) or, in addition, psychological support from a professional psychologist (experimental group). The psychological support was provided at the pre-operative visit, during the hospitalisation period and at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Two studies, one utilizing guided imagery and the other emotional counselling, measured quality of life using the Short Form (36) Health Questionnaire (SF‐36), assessing physical and mental components of this outcome at both subacute and longer term time‐points. Both studies independently reported statistically significant improvements in physical components of quality of life at both time points in the intervention groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies, one utilizing guided imagery and the other emotional counselling, measured quality of life using the Short Form (36) Health Questionnaire (SF‐36), assessing physical and mental components of this outcome at both subacute and longer term time‐points. Both studies independently reported statistically significant improvements in physical components of quality of life at both time points in the intervention groups.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies independently reported statistically significant improvements in physical components of quality of life at both time points in the intervention groups. Only one study found significant improvements in the mental component of quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Even patients without diagnosed anxiety disorder are often concerned about postoperative pain, being able to care for themselves, and mobility, especially if they live alone. A study of the effect of psychological support on patients indicated for primary TJA published by Tristano et al demonstrated that patients who received psychological support had a lower incidence of anxiety and depression than those who did not [10]. Additionally, THA patients who received psychological support reached their physical therapy goals 1.2 days sooner than those who did not receive any psychological support [10].…”
Section: Patient Selection and Screeningmentioning
confidence: 99%
“…A study of the effect of psychological support on patients indicated for primary TJA published by Tristano et al demonstrated that patients who received psychological support had a lower incidence of anxiety and depression than those who did not [10]. Additionally, THA patients who received psychological support reached their physical therapy goals 1.2 days sooner than those who did not receive any psychological support [10]. Patients being considered for OTJA, who are required to manage their own pain control, physical therapy, and self-care, are even more likely to benefit from a strong psychological support.…”
Section: Patient Selection and Screeningmentioning
confidence: 99%
See 1 more Smart Citation